Solid electrolyte and method for producing same, electrode for lithium ion battery, and lithium ion battery

A solid electrolyte with controlled X-ray diffraction peaks and a specific molar ratio of Li, Sb, S, and Br or I atoms, manufactured via freezing-drying and ion exchange, addresses the challenges of conductivity and efficiency in lithium-ion batteries, resulting in high-capacity batteries with enhanced safety.

JP7624207B2Active Publication Date: 2025-01-30TOYOHASHI UNIVERSITY OF TECHNOLOGY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021061804
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-01-30
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

Existing lithium-ion batteries face challenges in achieving high lithium-ion conductivity and manufacturing efficiency, particularly in the use of solid electrolytes, which are crucial for enhancing battery performance and safety.

Method used

The development of a solid electrolyte composed of specific compounds (Li5SBS5) with controlled X-ray diffraction peaks and a molar ratio of Li, Sb, S, and Br or I atoms, manufactured through a freezing-drying process and ion exchange method to enhance lithium-ion conductivity.

Benefits of technology

The resulting solid electrolyte exhibits superior lithium-ion conductivity, enabling high-capacity lithium-ion batteries with improved safety and manufacturing efficiency, avoiding the generation of hydrogen sulfide during production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624207000002
    Figure 0007624207000002
  • Figure 0007624207000003
    Figure 0007624207000003
  • Figure 0007624207000004
    Figure 0007624207000004
Patent Text Reader

Abstract

To provide a solid electrolyte excellent in lithium ion conductivity and its manufacturing method as well as a lithium ion battery having high charge and discharge capacity and an electrode for a lithium ion battery imparting the same.SOLUTION: A solid electrolyte of the present invention contains (1) a compound containing Li atoms, Sb atoms, S atoms and Br atoms, and having, in a spectrum obtained by XRD measurement using CuKα rays, diffraction peaks at least at diffraction angles of 2θ=(21.9±0.5) deg, (31.3±0.5) deg and (38.5±0.5) deg, or (2) a compound containing Li atoms, Sb atoms, S atoms and I atoms, and having, in the spectrum obtained by XRD measurement using CuKα rays, diffraction peaks at least at diffraction angles of 2θ=(21.3±0.5) deg, (23.8±0.5) deg and (32.3±0.5 ) deg.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid electrolyte suitable as a constituent material for a positive electrode or the like that constitutes a lithium ion battery, a method for producing the same, an electrode for a lithium ion battery, and a lithium ion battery. [Background technology]

[0002] In recent years, the development of lithium ion batteries, sodium ion batteries, lithium sulfur batteries, and the like, which are capable of achieving high energy density, has been vigorously pursued. Lithium-ion batteries are secondary batteries in which lithium ions are released from the positive electrode during charging, move to the negative electrode and are stored, and lithium ions are inserted from the negative electrode back into the positive electrode during discharging. Lithium-ion batteries have characteristics such as high energy density and long life, and so have been widely used as power sources for home appliances such as personal computers and cameras, portable electronic devices and communication devices such as mobile phones, and power tools, and more recently have been used in large batteries installed in electric vehicles (EVs) and hybrid electric vehicles (HEVs). In such lithium ion batteries, it is known that using a solid electrolyte instead of an electrolyte solution containing a flammable organic solvent not only simplifies safety devices but also leads to superior manufacturing costs, productivity, etc. In addition, solid electrolytes made of sulfides have high electrical conductivity (lithium ion conductivity) and are said to be useful for increasing the output of batteries. For example, a sulfide solid electrolyte having an argyrodite-type crystal structure is known.

[0003] Patent Document 1 describes the general formula Li + (12-n-x) B n+ X 2- 6-x Y - x Lithium arginine according to the present invention, n+ is selected from the group consisting of P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb and Ta; 2-is selected from the group consisting of S, Se and Te; Y - is selected from the group consisting of Cl, Br, I, F, CN, OCN, SCN, and N3, and 0≦x≦2, is disclosed, and it is stated that lithium arginine germanite can be used as a solid electrolyte in primary and secondary electrochemical energy storage. Patent Document 2 discloses a solid-state lithium secondary battery containing the lithium ion conductive material made of the lithium arginine germanite of Patent Document 1 in the positive electrode or solid electrolyte layer. Patent Document 3 discloses a method for producing a sulfide solid electrolyte having an argyrodite-type crystal structure, which includes a step of individually pulverizing two or more types of compounds or simple substances constituting a raw material mixture (lithium sulfide, phosphorus sulfide, lithium halide, etc.). Patent Document 4 also describes an ion-conductive material comprising: [A] a composite material containing phosphorus (P), sulfur (S), lithium (Li) and iodine (I), the weight ratio of P being 0.14 to 0.40 and the weight ratio of I being 0.03 to 0.30; [B] sulfur and / or a discharge product thereof; and [C] an ion-conductive material having a specific surface area of ​​1100 m. 2 / g or more of a conductive material, and is used in a positive electrode mixture layer of an all-solid-state lithium-sulfur battery. In addition, Non-Patent Document 1 discloses Li6SbS5I having an argyrodite-type crystal structure, which is obtained by mixing Li2S, Sb2S3, S, and LiI in a predetermined molar ratio and heating the mixture in a vacuum at 550°C for 100 hours. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2010-540396 [Patent Document 2] JP 2011-96630 A [Patent Document 3] JP 2018-206611 A [Patent Document 4] JP 2015-146281 A [Non-patent literature]

[0005] [Non-Patent Document 1] "Synthesis and Characterization of New Solid-State Li-Superionic Conductors" A thesis presented to the University of Waterloo in fulfillment of the thesis requirement for the degree of Master of Science in Chemistry-Nanotechnology, by Laidong Zhou. Waterloo, Ontario, Canada, 2017. Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a solid electrolyte having excellent lithium ion conductivity, a method for producing the same, a lithium ion battery having high charge / discharge capacity, and an electrode for the lithium ion battery which provides the same. [Means for solving the problem]

[0007] The present invention is illustrated below. [1] A solid electrolyte comprising the following compound (1) or (2): (1) A compound containing Li atoms, Sb atoms, S atoms, and Br atoms, which has diffraction peaks at at least diffraction angles 2θ=(21.9±0.5) deg, (31.3±0.5) deg, and (38.5±0.5) deg in an X-ray diffraction spectrum obtained by powder X-ray diffraction measurement using CuKα radiation (hereinafter referred to as "XRD measurement"). (2) A compound containing Li atoms, Sb atoms, S atoms, and I atoms, which has diffraction peaks at diffraction angles 2θ=(21.3±0.5) deg, (23.8±0.5) deg, and (32.3±0.5) deg in an X-ray diffraction spectrum obtained by XRD measurement. [2] In the above X-ray diffraction spectrum of the above compound (1), the maximum diffraction intensity at the diffraction angle 2θ=(31.3±0.5) deg is defined as the background intensity I A The maximum diffraction intensity of the diffraction peak at the diffraction angle 2θ = (21.9 ± 0.5) deg is I B Then, I B / I A The solid electrolyte according to the above [1], wherein the ratio is 0.4 to 1.3. [3] In the above X-ray diffraction spectrum of the above compound (2), the maximum diffraction intensity at the diffraction angle 2θ=(21.3±0.5) deg is taken as the background intensity I C The maximum diffraction intensity of the diffraction peak at the diffraction angle 2θ = (32.3 ± 0.5) deg is I D Then, I D / I C The solid electrolyte according to the above [1], wherein the ratio is 0.5 to 1.0. [4] The solid electrolyte according to any one of [1] to [3] above, wherein the compounds (1) and (2) are represented by the following formula (I): Li 5+m SbS5X n (I) (In the formula, X is a Br atom or an I atom, m is 0.9 to 1.1, and n is 0.9 to 1.1.) [5] An electrode for a lithium ion battery, comprising the solid electrolyte according to any one of [1] to [4] above. [6] A lithium ion battery comprising the lithium ion battery electrode according to [5] above. [7] A method for producing the solid electrolyte according to any one of [1] to [4] above, comprising the steps of: A method for producing a solid electrolyte, comprising the step of freeze-drying a solution in which Li5SbS5 and LiX (X is a Br atom or an I atom) are dissolved. [8] The method for producing a solid electrolyte according to [7] above, wherein the Li5SbS5 is synthesized by exchanging Na ions of Na5SbS5 for Li ions by a cation exchange method. Effect of the Invention

[0008] Although the compound (1) or (2) contained in the solid electrolyte of the present invention is a compound having a molar ratio of Li atoms, Sb atoms, S atoms and halogen atoms of about 6:1:5:about 1, it does not have an argyrodite structure and has lithium ion conductivity superior to that of a solid electrolyte made of a compound in which the halogen atoms are Cl atoms. Such a solid electrolyte is suitable for forming an electrode (preferably a positive electrode) that provides a lithium ion battery with a high charging capacity. According to the method for producing a solid electrolyte of the present invention, denaturation is suppressed compared to other desolvation means, and a solid electrolyte having excellent lithium ion conductivity can be efficiently produced. When Na ions of Na5SbS5 are exchanged for Li ions to produce Li5SbS5 by a cation exchange method, hydrogen sulfide is not generated in the production process, so the work can be carried out safely. [Brief description of the drawings]

[0009] [Figure 1] 1 is an X-ray diffraction spectrum of a solid electrolyte containing compound (1) or (2). [Diagram 2] 1 shows X-ray diffraction spectra of the solid electrolytes obtained in Examples 1-1 to 1-4 and Comparative Example 1-1. [Diagram 3] 1 is a graph showing the temperature dependence of electrical conductivity of the solid electrolytes obtained in Examples 1-1 and 1-4 and Comparative Examples 1-1 and 1-2. [Figure 4] FIG. 2 is a schematic cross-sectional view showing a measurement cell for charging tests including a lithium ion battery prepared in the Examples. [Diagram 5] 2 is a graph showing the charge / discharge characteristics of the lithium ion battery obtained in Example 2-1. [Figure 6] 1 is a graph showing the charge / discharge characteristics of the lithium ion battery obtained in Example 2-2. [Figure 7] 1 is a graph showing the charge / discharge characteristics of the lithium ion battery obtained in Comparative Example 2-1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The solid electrolyte of the present invention contains the following compound (1) or (2): (1) A compound containing Li atoms, Sb atoms, S atoms, and Br atoms, and having diffraction peaks at diffraction angles 2θ=(21.9±0.5) deg, (31.3±0.5) deg, and (38.5±0.5) deg in an X-ray diffraction spectrum obtained by XRD measurement. (2) A compound containing Li atoms, Sb atoms, S atoms, and I atoms, and having diffraction peaks at diffraction angles 2θ=(21.3±0.5) deg, (23.8±0.5) deg, and (32.3±0.5) deg in an X-ray diffraction spectrum obtained by XRD measurement.

[0011] The above compounds (1) and (2) are preferably represented by the following formula (I). Li 5+m SbS5X n (I) (In the formula, X is a Br atom or an I atom, m is 0.9 to 1.1, and n is 0.9 to 1.1.)

[0012] The compound (1) is a compound in which X in the formula (I) is a Br atom, and from the viewpoint of lithium ion conductivity, m is particularly preferably 0.95 to 1.10 and n is 0.95 to 1.05. The compound (2) is a compound in which X in the formula (I) is an I atom, and from the viewpoint of lithium ion conductivity, it is particularly preferable that m is 0.95 to 1.10 and n is 0.95 to 1.05.

[0013] The X-ray diffraction spectra of the above compounds (1) and (2) are shown in Figure 1, where (1-1) is the X-ray diffraction spectrum of Li5SbS5Br, an example of compound (1), and (2-1) is the X-ray diffraction spectrum of Li5SbS5I, an example of compound (2). In either case, no diffraction peaks specific to the argyrodite-type crystal structure (diffraction peaks at 2θ = 25.0 deg and 30.0 deg) are observed, and therefore the above compounds (1) and (2) do not have an argyrodite-type crystal structure. FIG. 1 also shows the X-ray diffraction spectrum of Li5SbS5Cl in which Cl atoms are substituted for the Br and I atoms, but it is completely different from the X-ray diffraction spectra of (1-1) and (2-1) above.

[0014] In FIG. 1, the X-ray diffraction spectrum of (1-1) shows diffraction peaks at (21.9±0.5) deg, (31.3±0.5) deg, and (38.5±0.5) deg, with the diffraction peak at (31.3±0.5) deg being the most intense and the diffraction peak at (21.9±0.5) deg being the second most intense. In the compound (1) according to the present invention, the maximum diffraction intensity at the position of (31.3±0.5) deg is taken as the background intensity I A The maximum diffraction intensity of the diffraction peak at the position of (21.9±0.5) deg is I B From the viewpoint of lithium ion conductivity, I B / I A The ratio is preferably 0.4 to 1.3, and more preferably 0.4 to 0.7.

[0015] In FIG. 1, the X-ray diffraction spectrum of (2-1) shows diffraction peaks at (21.3±0.5) deg, (23.8±0.5) deg, and (32.3±0.5) deg, with the diffraction peak at (21.3±0.5) deg being the most intense and the diffraction peak at (32.3±0.5) deg being the second most intense. In the compound (2) according to the present invention, the maximum diffraction intensity at the position of (21.3±0.5) deg is taken as the background intensity I CThe maximum diffraction intensity of the diffraction peak at the position of (32.3±0.5) deg is I D From the viewpoint of lithium ion conductivity, I D / I C The ratio is preferably 0.5 to 1.0, and more preferably 0.5 to 0.8.

[0016] The solid electrolyte of the present invention can be produced by preparing a solution in which Li5SbS5 and LiX (X is a Br atom or an I atom) are dissolved, and then removing the solvent from the solution using a conventionally known method. Examples of the removal method include freeze-drying (a method in which a solution is first frozen, and then the boiling point of the frozen dried product is lowered in a vacuum to sublimate the solvent in the dried product), heat-reduced-pressure drying (a method in which the boiling point is lowered by reducing the pressure inside a heating device to promote solvent removal), and spray-drying (a method in which a solution is sprayed into a gas and rapidly dried to obtain a dry powder).

[0017] The method for producing a solid electrolyte of the present invention (hereinafter referred to as "the method for producing a solid electrolyte of the present invention") includes a step of freeze-drying a solution in which Li5SbS5 and LiX (X is a Br atom or an I atom) are dissolved (hereinafter referred to as "the freeze-drying step").

[0018] In the freeze-drying step, a solution of Li5SbS5 and LiX prepared in advance is used. The solvent of this solution is not particularly limited as long as it dissolves Li5SbS5 and LiX. Preferred solvents are water, alcohol, and the like, and water is particularly preferred. The molar ratio of Li5SbS5 and LiX is preferably 30-95:5-70, more preferably 45-55:45-55, from the viewpoint of the production efficiency of the above compounds (1) and (2). The total concentration of Li5SbS5 and LiX in the above solution is preferably 0.1 to 20 mass %, more preferably 0.5 to 10 mass %, from the viewpoints of the workability in the freeze-drying step and the yield of the solid electrolyte.

[0019] In the freeze-drying step, it is preferable to freeze the solution of Li5SbS5 and LiX at -40°C to -20°C for 20 to 50 hours, and then dry it at 120°C to 160°C for 1 to 3 hours. The freezing may be performed under normal pressure or reduced pressure. The inventors presume that the compounds (1) and (2) are not formed in the prepared solution of Li5SbS5 and LiX, but are formed during the freezing of the solution, and the structure of the compounds (1) and (2) can be kept in a metastable state by maintaining the solution at the above freezing temperature. In addition, depending on the processing conditions of the freeze-drying step, the compound becomes porous, and when it is used as a component of the electrolyte layer, etc., it is expected to have an effect of mitigating the volume change of the lithium ion battery.

[0020] The method for producing a solid electrolyte of the present invention may include, after the freeze-drying step, a heat treatment step, a pulverization step, etc., as necessary. When both the heat treatment step and the pulverization step are performed, the order of these steps is not particularly limited, and these steps may be performed simultaneously. The heat treatment conditions in the heat treatment step are not particularly limited. The temperature is appropriately selected depending on the composition of the compounds (1) and (2), and is preferably 300°C or less, more preferably 70°C to 200°C, and even more preferably 105°C to 150°C. The heat treatment may be performed under normal pressure or reduced pressure. The atmosphere may be dry air, nitrogen, argon, etc. In the pulverization step, a known pulverizer capable of pulverizing the material into fine particles can be used.

[0021] In the present invention, Li5SbS5 used in the freeze-drying step is preferably synthesized by exchanging Na ions of Na5SbS5 with Li ions by a cation exchange method. There are various methods for synthesizing Li5SbS5, but when Li2S, SbS2, and S are used as starting materials, for example, H2S is generated when the materials come into contact with moisture, so it is necessary to handle it in an absolutely dry environment. However, when Na5SbS5 is made into an aqueous solution and this is subjected to a cation exchange method to exchange Na ions of Na5SbS5 with Li ions to synthesize Li5SbS5, no H2S is generated and it can be handled in the air.

[0022] In the above cation exchange method, it is preferable to pass the Na5SbS5 aqueous solution through an ion exchange resin tower loaded with a strongly acidic cation exchange resin containing Li ions. This allows the Li5SbS5 aqueous solution to be recovered and then dehydrated to obtain Li5SbS5. The temperature during cation exchange is not particularly limited, and is preferably 10°C to 50°C. In addition, the SV value (space velocity: the value obtained by dividing the amount of Na5SbS5 aqueous solution passed by the volume of the cation exchange resin) is preferably 5 or less, more preferably 2 or less, from the viewpoint of exchange efficiency. The method for preparing the Na5SbS5 aqueous solution is not particularly limited, and may be, for example, a method in which Na3SbS4 and Na2S are dissolved in water (e.g., ion-exchanged water). Na3SbS4 can be obtained, for example, by weighing out Na2S, SbS2, and S as starting materials according to a predetermined molar ratio, dissolving them in ion-exchanged water, adding acetone to precipitate Na3SbS4 hydrate, and then collecting the precipitate by filtration and removing the solvent.

[0023] The solid electrolyte of the present invention is suitable as a constituent material of an electrode of a lithium ion battery (electrode for lithium ion batteries), that is, as an active material. In the present invention, as shown in Fig. 4, the lithium ion battery generally includes a positive electrode 21 and a negative electrode 23, which are electrodes for lithium ion batteries, and an electrolyte layer 25 disposed between the positive electrode 21 and the negative electrode 23. The lithium ion battery may further include a positive electrode current collector that collects current from the positive electrode 21 and a negative electrode current collector that collects current from the negative electrode 23 (not shown).

[0024] The lithium ion battery electrode of the present invention may be either a positive electrode or a negative electrode, and contains the above-mentioned solid electrolyte of the present invention, and may further contain other conventionally known solid electrolytes, if necessary.

[0025] The lithium ion battery electrode of the present invention may contain, in addition to the solid electrolyte, a binder, a conductive assistant, and the like.

[0026] Examples of the binder include fluorine-containing resins such as polytetrafluoroethylene (PTFE), polyhexafluoropropylene (PHFP), polyvinylidene fluoride (PVdF), and vinylidene fluoride-hexafluoropropylene copolymers; polyolefin resins such as polypropylene and polyethylene; ethylene-propylene-non-conjugated diene rubbers (EPDM, etc.), sulfonated EPDM, and natural butyl rubber (NBR).

[0027] The conductive assistant may be made of a carbon material, a metal powder, a metal compound, etc., and among these, a carbon material is preferably used. Examples of the carbon material include plate-shaped conductive materials such as graphene; linear conductive materials such as carbon nanofibers and carbon nanotubes; carbon black such as Ketjen Black, Acetylene Black, Denka Black (trade name), Thermal Black, and Channel Black; and granular conductive materials such as graphite.

[0028] The lithium ion battery electrode of the present invention is particularly suitable as a positive electrode 21 of a lithium ion battery 20 shown in Fig. 4. In this case, the contents of the solid electrolyte and conductive assistant contained in the positive electrode, when the total of these is taken as 100 mass%, are preferably 50 to 98 mass% and 2 to 50 mass%, more preferably 70 to 95 mass% and 5 to 30 mass%, respectively.

[0029] The thickness of the positive electrode in the current-carrying direction is not particularly limited, but is usually 5 μm or more, and preferably 20 μm to 0.5 mm.

[0030] When the lithium ion battery of the present invention includes the lithium ion battery electrode of the present invention as a positive electrode, the configuration of the negative electrode is not particularly limited.

[0031] The negative electrode essentially contains a negative electrode active material, and may further contain a binder, a conductive assistant, other solid electrolytes, etc. Examples of the negative electrode active material include carbon materials; metals such as lithium, indium, aluminum, and silicon, and alloys containing these metals.

[0032] The thickness of the negative electrode in the current-carrying direction is not particularly limited, but is usually 1 μm or more, and preferably 10 μm to 0.5 mm.

[0033] The electrolyte layer is not particularly limited as long as it contains a solid electrolyte, but it is preferable that the electrolyte layer is substantially made of a solid electrolyte. Examples of the solid electrolyte include Li2S-P2S5-based solid electrolytes, Li2S-P2S5-LiX 1 system solid electrolyte (X 1 is a Cl atom, Br atom, or I atom), and Li with a perovskite structure 3x La 2 / 3―x TiO3(LLTO), Li7La3Zr2O with garnet structure 12 (LLZO), LiTi2(PO4)3(LTP) with NASICON type crystal structure, Li called LISICON 3.5 Zinc 0.25 GeO4, amorphous oxynitride-based lithium ion conductor Li 3.3 PO3.9 N 0.17 (LiPON), and lithium borohydride LiBH4.

[0034] The thickness of the electrolyte layer in the current-carrying direction is not particularly limited, but is usually 1 μm or more, and preferably 10 μm to 0.5 mm.

[0035] When the lithium ion battery of the present invention is provided with a positive electrode current collector or a negative electrode current collector, the constituent material thereof may be, for example, stainless steel, gold, platinum, copper, zinc, nickel, tin, aluminum, or an alloy thereof, and may have a plate-like, foil-like, mesh-like, or the like shape.

[0036] When the lithium ion battery of the present invention is provided with electrodes containing the solid electrolyte of the present invention, it has excellent charge / discharge characteristics. EXAMPLES

[0037] 1. Manufacturing raw materials The raw materials used in the production of the solid electrolyte and the like are as follows. (1) Antimony sulfide (SbS2) powder The product used was "SbS2" (trade name) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. The purity was 98%. (2) Sodium sulfide (Na2S) powder The product used was "Na2S" (trade name) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. The purity was 98%. (3) Sulfur (S) powder The product used was "S" (product name) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. The purity was 98% and the particle size was approximately 50 μm. (4) Lithium iodide (LiI) powder The product used was "LiI" (trade name) manufactured by Sigma-Aldrich. It has a purity of 99% and a particle size of approximately 500 μm. (5) Lithium bromide (LiBr) powder The product used was "LiBr" (trade name) manufactured by Sigma-Aldrich. It has a purity of 99% and a particle size of approximately 100 μm. (6) Lithium sulfide (Li2S) powder The product used was "Li2S" (product name) manufactured by Mitsuwa Chemical Co., Ltd. The purity was 99.9% and the particle size was approximately 50 μm.

[0038] (7) Li5SbS5-containing aqueous solution (Li5SbS5 concentration: 3.3 g / L) This material was prepared by the following method. 3.2g of SbS2 powder, 3.0g of Na2S powder, and 0.9g of S powder were added to 90mL of ion-exchanged water and stirred at 70℃ for 2 hours. After filtering the reaction solution, 20mL of acetone was added and the mixture was left to stand at 5℃ for 48 hours to obtain a precipitate of Na3SbS4 hydrate. The precipitate was then collected by filtration and dried under reduced pressure at 140℃ for 2 hours to obtain Na3SbS4 powder. Then, 0.5g of this Na3SbS4 powder and 0.12g of Na2S were dissolved in 50mL of ion-exchanged water to obtain a Na5SbS5 aqueous solution. Next, 50 mL of this Na5SbS5 aqueous solution was passed through an ion exchange resin tower loaded with about 20 g of a cation exchange resin in which the counter ion of Mitsubishi Chemical's strong acid cation exchange resin "IR120B Na" (trade name) had been changed to Li ion with LiOH, to obtain an aqueous solution containing Li5SbS5 (light yellow). In addition, about 150 mL of ion exchange water was used to push out the aqueous solution remaining in the ion exchange resin tower. During this series of operations, no odor of hydrogen sulfide was detected.

[0039] 2. Production and evaluation of solid electrolytes A solid electrolyte was produced using the above-mentioned raw materials, and the electrical conductivity was measured.

[0040] Example 1-1 (Production of solid electrolyte of Li6SbS5Br) 150 mL of the Li5SbS5-containing aqueous solution was mixed with 1.36 mL of a 0.1 g / mL LiBr aqueous solution, and the mixture was concentrated in an evaporator to a total volume of about 20 mL. During this operation, no odor of hydrogen sulfide was detected. Thereafter, this concentrated liquid was frozen at -30°C, freeze-dried, and further dried under reduced pressure at 140°C for 1 hour to obtain a solid electrolyte containing Li6SbS5Br (hereinafter referred to as "solid electrolyte (S1)").

[0041] The obtained solid electrolyte (S1) was subjected to powder X-ray diffraction measurement (ray source: CuKα) to obtain the X-ray diffraction spectrum shown in Fig. 2. According to Fig. 2, diffraction peaks were confirmed at diffraction angles 2θ=14.0 deg, 22.0 deg, 31.3 deg, and 38.5 deg, and no diffraction peaks were observed at around 2θ=25.0 deg and 30.0 deg, which are specific to an argyrodite-type crystal structure.

[0042] In the X-ray diffraction spectrum of Fig. 2, the maximum diffraction intensity at the diffraction angle 2θ = 31.3 deg is the background intensity I A The maximum diffraction intensity of the diffraction peak at the diffraction angle 2θ = 21.9 deg is I B When I B / I A The ratio was calculated to be 545cps / 1093cps=0.50.

[0043] Next, the electrical conductivity of the obtained solid electrolyte (S1) at 25° C. to 170° C. was measured by the following method. The solid electrolyte was cut into a disk-shaped test piece (size: radius 5 mm x height 0.6 mm) using a uniaxial hydraulic press, and placed in a measurement unit (glass container) under an argon gas atmosphere. A ribbon heater connected to a temperature regulator and a heat insulating material were wrapped around the measurement unit (glass container). The conductivity was measured at about 23°C, about 55°C, about 75°C, about 95°C, about 115°C, about 135°C, and about 155°C by an AC method using an IMPEDANCE ANALYZER "S1260" (model name) manufactured by SOLATRON. The conductivity was measured after heating the test piece and setting each measurement temperature from the low temperature side and leaving it to stand for 1 hour, but since the same test piece was used, the measurement temperature was measured in ascending order of temperature, at about 23°C, then heated to about 55°C, measured after 1 hour, and then heated to about 75°C, and so on, and the conductivity was measured up to 155°C. The electrical conductivity at each temperature is shown in FIG.

[0044] Example 1-2 (Li 5.9 SbS5Br 0.9 (Production of solid electrolytes) The same procedure as in Example 1-1 was carried out, except that the amount of the LiBr aqueous solution used was changed to 1.23 mL. 5.9 SbS5Br 0.9 A solid electrolyte (hereinafter referred to as "solid electrolyte (S2)") containing the above was obtained. Then, the X-ray diffraction measurement of this solid electrolyte (S2) was performed (see FIG. 2).

[0045] In the X-ray diffraction spectrum of Fig. 2, the maximum diffraction intensity at the diffraction angle 2θ = 31.3 deg is the background intensity I A The maximum diffraction intensity of the diffraction peak at the diffraction angle 2θ = 21.9 deg is I B When I B / I A The ratio was calculated to be 337cps / 455cps=0.74.

[0046] Example 1-3 (Li 6.1 SbS5Br 1.1 (Production of solid electrolytes) The same procedure as in Example 1-1 was carried out, except that the amount of the LiBr aqueous solution used was changed to 1.50 mL. 6.1 SbS5Br 1.1 A solid electrolyte (hereinafter referred to as "solid electrolyte (S3)") containing the above was obtained. Then, the X-ray diffraction measurement of this solid electrolyte (S3) was performed (see FIG. 2).

[0047] In the X-ray diffraction spectrum of Fig. 2, the maximum diffraction intensity at the diffraction angle 2θ = 31.3 deg is the background intensity I A The maximum diffraction intensity of the diffraction peak at the diffraction angle 2θ = 21.9 deg is I B When I B / I A The ratio was calculated to be 291cps / 234cps=1.24.

[0048] Example 1-4 (Production of Li6SbS5I solid electrolyte) A solid electrolyte containing Li6SbS5I (hereinafter referred to as "solid electrolyte (S4)") was obtained by the same operation as in Example 1-1, except that the LiBr aqueous solution was changed to a 0.1 g / mL LiI aqueous solution. Then, the X-ray diffraction measurement and the electrical conductivity measurement of this solid electrolyte (S4) were performed (see FIG. 2, FIG. 3, and Table 1).

[0049] In the X-ray diffraction spectrum of Fig. 2, the maximum diffraction intensity at the diffraction angle 2θ = 21.3 deg is the background intensity I C The maximum diffraction intensity of the diffraction peak at the diffraction angle 2θ = 32.2 deg is I D When I D / I C The ratio was calculated to be 645cps / 830cps=0.78.

[0050] The electrical conductivity of this solid electrolyte (S4) was measured at 154.5°C, then cooled to 17.6°C (1 / T = 3.44) and measured again. The electrical conductivity was 6.5 × 10 -8 S / cm, and it was confirmed that the change was reversible before and after cooling.

[0051] In addition, when the conductivity was measured by the DC method using the same configuration, it was 2.2 × 10 at 54.5°C (1000 / T (T is the absolute temperature in K) = 3.05). -6 The DC method showed that the conductivity was due to electronic conduction alone, and a comparison with the AC method showed that the material was mainly ionic, but also had electronic conductivity. This is an advantageous property for a positive electrode composite.

[0052] Comparative Example 1-1 (Production of Li3SbS4 solid electrolyte) 3.2g of SbS2 powder, 3.0g of Na2S powder, and 0.9g of S powder were added to 90mL of ion-exchanged water and stirred at 70℃ for 2 hours. The obtained reaction liquid (liquid containing Na3SbS4) was passed through an ion-exchange resin tower loaded with about 20g of a cation-exchange resin in which the counter ion of the strong acid cation-exchange resin "IR120B Na" (trade name) manufactured by Mitsubishi Chemical Corporation was changed to Li ion with LiOH, to obtain an aqueous solution containing Li3SbS4. Next, this aqueous solution was concentrated, frozen at -30℃, freeze-dried, and further dried under reduced pressure at 140℃ for 1 hour to obtain a solid electrolyte containing Li3SbS4 (hereinafter referred to as "solid electrolyte (T1)"). Then, X-ray diffraction measurement and electrical conductivity measurement of this solid electrolyte (T1) were performed (see Fig. 2, Fig. 3, and Table 1). As is clear from FIG. 3, the electrical conductivity of the solid electrolyte (T1) is inferior to the electrical conductivity of the solid electrolytes (S1) and (S4).

[0053] Comparative Example 1-2 (Production of solid electrolyte to be Li6SbS5Cl) A solid electrolyte containing Li6SbS5Cl (hereinafter referred to as "solid electrolyte (T2)") was obtained by the same operation as in Example 1-1, except that the LiBr aqueous solution was changed to a 0.1 g / mL LiCl aqueous solution. Then, the X-ray diffraction measurement and the electrical conductivity measurement of this solid electrolyte (T2) were performed (see FIG. 2, FIG. 3, and Table 1). As is clear from FIG. 3, the electrical conductivity of the solid electrolyte (T2) is inferior to the electrical conductivity of the solid electrolytes (S1) and (S4).

[0054] [Table 1]

[0055] 3. Manufacturing and evaluation of positive electrodes and lithium-ion batteries A composite for a positive electrode containing the solid electrolyte (S1) obtained in Example 1-1, the solid electrolyte (S4) obtained in Example 1-4, or Li7P2S8I, which is a conventionally known solid electrolyte, was prepared, and then, a lithium ion battery having a positive electrode was prepared using each composite for a positive electrode. Next, a test cell 10 shown in FIG. 4 including the obtained lithium ion battery was produced, and a charging test was carried out.

[0056] Example 2-1 The solid electrolyte (S1) obtained in Example 1-1 and carbon nanofibers (diameter: 0.1 μm, length: 20 μm) serving as an electronic conductive assistant were mixed in amounts of 90 mg and 10 mg, respectively, to obtain a composite for a positive electrode. Next, the solid electrolyte (S1) was subjected to pressure molding using a uniaxial hydraulic press to obtain a disk-shaped preform (radius: 5 mm, thickness: 0.5 mm). Then, in a state where this preform for the electrolyte layer was housed inside a cylindrical body 27 made of polyether ether ketone (PEEK), about 5 mg of the positive electrode composite obtained above was filled on the entire surface side of one of the surfaces, and pressure molding was performed using a uniaxial hydraulic press. Furthermore, a Li-In alloy foil (thickness 0.1 mm, diameter 5 mm) was attached to the other surface of the preform for the electrolyte layer, and an all-solid-state lithium ion battery 20 was obtained, which includes a positive electrode 21 (thickness about 30 μm) made of the positive electrode composite, an electrolyte layer 25 made of the solid electrolyte (S1), and a negative electrode 23 made of a Li-In alloy. Then, stainless steel-nickel conductive parts were inserted from the top and bottom of the cylindrical body 27 housing the lithium ion battery 20, and fixed with a jig to obtain the measurement cell 10 shown in FIG. 4. Then, the measurement cell 10 was sealed in a glass container (not shown), and the gas in the glass container was replaced with argon gas, and a charge / discharge test was performed. The glass container containing the measurement cell 10 was placed in an electric furnace set at 60°C or 70°C, and the charge / discharge test was performed using a charge / discharge device "BTS-2004H" (model name) manufactured by NAGANO under the conditions of 0.8-2.4V vs Li-In, C rate: 0.1C. The results are shown in FIG. 5.

[0057] Example 2-2 A positive electrode composite was obtained in the same manner as in Example 2-1, except that the solid electrolyte (S4) was used instead of the solid electrolyte (S1). Thereafter, this positive electrode composite was used to obtain a lithium ion battery 20 including a positive electrode 21 in the same manner as in Example 2-1. A charge / discharge test was then carried out in the same manner as in Experimental Example 2-1. The results are shown in FIG.

[0058] Comparative Example 2-1 A lithium ion battery 20 including a positive electrode 21 was obtained in the same manner as in Example 2-1, except that a positive electrode composite consisting of a mixture of 100 mg of Li7P2S8I, 9.3 mg of Li2S, and 12.1 mg of carbon nanofiber ("VGCF" manufactured by Showa Denko K.K.) was used instead of the positive electrode composite of Example 2-1. Then, a charge / discharge test was performed in the same manner as in Experimental Example 2-1. The results are shown in FIG.

[0059] As is clear from Fig. 7, the lithium ion battery of Comparative Example 2-1 did not have satisfactory charge / discharge characteristics. On the other hand, as can be seen from Figs. 5 and 6, in Examples 2-1 and 2-2 in which electrodes containing the solid electrolyte according to the present invention were used, lithium ion batteries with excellent charge / discharge characteristics were obtained. [Industrial Applicability]

[0060] The solid electrolyte of the present invention is suitable as a power source for home electric appliances such as personal computers and cameras, power storage devices, portable electronic devices or communication devices such as mobile phones, electric tools such as power tools, and further as a constituent material of lithium ion batteries constituting large batteries mounted on electric vehicles (EVs), hybrid electric vehicles (HEVs), etc., i.e., a constituent material of electrodes or electrolyte layers for lithium ion batteries. [Explanation of symbols]

[0061] 10: Measurement cell for charging test 20: Lithium-ion battery 21: Positive electrode 23: Negative electrode 25: Electrolyte layer 27: PEEK cylindrical body 31: Retaining plate 33: Presser pin 35: Clamping screw 37: Kapton (registered trademark) tape

Claims

1. A solid electrolyte comprising the following compound (1) or (2): (1) A compound containing Li atoms, Sb atoms, S atoms, and Br atoms, which has diffraction peaks at at least diffraction angles 2θ=(21.9±0.5) deg, (31.3±0.5) deg, and (38.5±0.5) deg in an X-ray diffraction spectrum obtained by powder X-ray diffraction measurement using CuKα radiation. (2) A compound containing Li atoms, Sb atoms, S atoms, and I atoms, which has diffraction peaks at at least diffraction angles 2θ=(21.3±0.5) deg, (23.8±0.5) deg, and (32.3±0.5) deg in an X-ray diffraction spectrum obtained by powder X-ray diffraction measurement using CuKα radiation.

2. In the X-ray diffraction spectrum of the compound (1), the maximum diffraction intensity at a diffraction angle 2θ=(21.9±0.5) deg is defined as the background intensity I A The maximum diffraction intensity of the diffraction peak at the diffraction angle 2θ = (31.3 ± 0.5) deg is I B Then, I B / I A The solid electrolyte according to claim 1, wherein the ratio is 0.4 to 1.

3.

3. In the X-ray diffraction spectrum of the compound (2), the maximum diffraction intensity at a diffraction angle 2θ=(32.3±0.5) deg is defined as the background intensity I C The maximum diffraction intensity of the diffraction peak at the diffraction angle 2θ = (21.3 ± 0.5) deg is I D Then, I D / I C 2. The solid electrolyte according to claim 1, wherein the ratio is 0.5 to 1.

0.

4. The solid electrolyte according to any one of claims 1 to 3, wherein the compounds (1) and (2) are represented by the following formula (I): Li 5+m SbS 5 X n (I) (In the formula, X is a Br atom or an I atom, m is 0.9 to 1.1, and n is 0.9 to 1.1.)

5. An electrode for a lithium ion battery, comprising the solid electrolyte according to claim 1 .

6. A lithium ion battery comprising the lithium ion battery electrode according to claim 5.

7. A method for producing the solid electrolyte according to any one of claims 1 to 4, comprising the steps of: Li 5 SbS 5 and freeze-drying a solution in which LiX (X is a Br atom or an I atom) is dissolved.

8. The Li 5 SbS 5 However, by cation exchange method, Na 5 SbS 5 8. The method for producing a solid electrolyte according to claim 7, wherein the solid electrolyte is synthesized by exchanging Na ions of the above formula (1) with Li ions.

Citation Information

Patent Citations

  • Lithium silver sulfide germanium ore

    JP2010540396A

  • Solid-state lithium secondary battery, and method for producing the same

    JP2011096630A

  • Positive electrode mixture and all-solid type lithium sulfur battery

    JP2015146281A

  • Method for producing sulfide solid electrolyte having argyrodite type crystal structure

    JP2018206611A

  • Method for manufacturing ion conductor for solid electrolyte

    JP2019102355A